Wnioski reductio ad absurdum wykładni art. 165 § 1 pkt 2 k.k. w kontekście zwalczania środków zastępczych - Gmerek, Mateusz (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
The study includes the analysis of the interpretation of Article 165 § 1 point 2 of the Criminal Code in the context of fighting designer drugs, expressed notionally as narcotic replacement drugs, specified in the 2005 Act on prevention of drug abuse. Interpretative doubts occurring in this scope were shown by quoting selected rulings. The paper presents the reductio ad absurdum conclusions resulting from judicial decisions and their meaning for the decisions made by common courts.
Keywords: reductio ad absurdum conclusions; narcotic replacement drugs; designer drugs; launch; psychoactive substances; intoxicants; drugs